1997
DOI: 10.1016/s0370-2693(97)01126-x
|View full text |Cite
|
Sign up to set email alerts
|

Colour-octet contributions to photoproduction via fragmentation at HERA

Abstract: We study J/ψ photoproduction via fragmentation at next-to-leading order in the QCD-improved parton model, using the nonrelativistic factorization formalism proposed by Bodwin, Braaten, and Lepage. We consider direct and resolved photoproduction of prompt J/ψ mesons and χ cJ mesons radiatively decaying to J/ψ + γ, taking into account the formation of both color-singlet and color-octet cc states. Adopting the values of the long-distance color-octet matrix elements extracted from fits to prompt-J/ψ data recently … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…So various efforts have been made to confirm this mechanism, or to fix the magnitudes of the universal NRQCD matrix elements. Although it seems to show qualitative agreements with experimental data, there are certain difficulties in the quantitative estimate in NRQCD for J/ψ photoproduction at the DESY ep collider HERA [5][6][7][8][9][10], J/ψ(ψ ′ ) and Υ polarization of hadronproduction at the Fermilab Tevatron, and J/ψ production in B-factories. A review of the situation could be found in Ref.…”
Section: Introductionmentioning
confidence: 91%
“…So various efforts have been made to confirm this mechanism, or to fix the magnitudes of the universal NRQCD matrix elements. Although it seems to show qualitative agreements with experimental data, there are certain difficulties in the quantitative estimate in NRQCD for J/ψ photoproduction at the DESY ep collider HERA [5][6][7][8][9][10], J/ψ(ψ ′ ) and Υ polarization of hadronproduction at the Fermilab Tevatron, and J/ψ production in B-factories. A review of the situation could be found in Ref.…”
Section: Introductionmentioning
confidence: 91%
“…Polarisation observables were subsequently predicted [283]. By analogy with hadroproduction, CO fragmentation channels were studied [277,339,278] but were shown to be relevant only for P T > 10 GeV, thus outside the region covered by the HERA data. Until the advent of NLO analyses including the CO contributions, the situation could well be summarised by Fig.…”
Section: ψ Photoproductionmentioning
confidence: 99%
“…Fragmentation contributions in photon-gluon fusion [120][121][122] exist only at the next order in α s and are suppressed for p t ∼ < 10 GeV. The cc[8, 3 S 1 ]-channel is insignificant for the direct-photon contribution, but dominates in resolved-photon interactions at p t ∼ > 5 GeV because it includes a gluon fragmentation component.…”
Section: Photoproduction Mechanismmentioning
confidence: 99%